الإعداد الإيماني للامة في ضؤ القران والسنة - Thaker Khayre Hamed ِAlsari
This research discusses how to prepare Muslims; from the point of strengthening the faith, according to the Qur'anic methodology, and the Sunnah. These issues are summarized: on the weakness of the people, their fall and disunity, and the need to rise to restore their glory and honor. Therefore, the way extracted from the Quran and the Sunnah is to prepare them based on the six pillars of Faith, as well as the most basic first step of spiritual and material preparation. The main purpose of this study was to discuss how to prepare the faith and strengthen the faith of Muslims by following the six pillars of faith, according to the Quranic guidelines. using deductive methodology to refine the verses of the Quran and also the hadith that guide the preparation of the people from the point of faith. Researchers also use the main analytical descriptive approach, which relies on key references from interpretive books and enlightenment. Researchers then used a deductive approach to developing the Qur'anic methodology in preparing the people from a religious standpoint, by extracting meaning, and explaining it in contemporary dimensions. This research has concluded many things, the main one is that the people should be prepared according to the Qur'an's mold, not with any other imported form. Preparing the people from the point of faith in Allah: is a condition for guidance, and a source of peace, tranquility, victory, glory, and strength. Preparing the people from the point of faith shaped by the destiny of good and bad: it produces strength in terms of godliness, happiness and peace, patience in the face of adversity, in giving the people strength. courage and patience in the face of adversity, as well as the resilience in dealing with adversity. as well as motivating they worked hard. Preparing the people from the point of faith to the Prophet Muhammad: as a role model in their patience and wisdom and in their moral principles. Preparing the people from the point of faith to the pamphlet(message) provides guidance on the accuracy of the monotheism and the specific protection of unbelief and error. Preparing the people from the angle of faith to the Angle (Malaikah): giving them love and a desire to emulate their morals. Preparing the people from the point of faith to the Hereafter: producing discipline, sincerity, doing good, establishing a balanced view of this world's life and expressing confidence in the justice of Allah: Researchers have come to the idea of establishing a strong institution for the preparation of the people in faith, moral and material to the good of the people, and the return of that glory. Alhamdulillah for all the praise of Allah who always gives His favor.